PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN SAMPAH DI DESA JATI KULON KABUPATEN KUDUS - Mantovani, As Sabilla Haqqi; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Community empowerment is a process of improving the ability and attitude of community self-reliance, in which the previously powerless communities become empowered. Community empowerment is being intensively implemented in villages in Indonesia, such as in Jati Kulon Village, Kudus Regency. The empowerment form in Jati Kulon Village of Kudus Regency is community empowerment through waste management. Waste management in question is to recycle organic waste to be used as various kinds of handicrafts that have a high enough selling value. The government of Jati Kulon Village, Kudus Regency also created a Waste Management Community namely â€œPaguyuban Pengelolaan Sampahâ€ to transport the garbage in the village area. This research uses descriptive qualitative research method that describes detailed description about observed phenomenon. Community empowerment through waste management in the village of Desa Jati Kulon, Kudus Regency is explained by looking at 3 (three) points in every community empowerment called â€œ3 Binaâ€ namely Human Train, Business Development and Environment Development. Support and good coordination from community, stakeholders, village institutions, and related parties will realize successful community empowerment and can prosper the community.